(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In present scenario regarding women entrepreneurship in India, we do not have the figures to show how many women’s are working as a entrepreneurs and how many women enterprises are in operation either in country or in any of the states. So it is very difficult to assess the development women entrepreneurship in India. Some rough data for three states indicates that there are about 1000 women enterprises in Karnataka, 700 in Gujarat and 500 in Tamil Nadu. It will be affair generation that while women constitute about 50 percent of our population, the proportion of enterprises set up and run by women is a fraction of 1 percent. The study of women as a entrepreneur is of crucial importance because the economic role that women play cannot be isolated from their total well being. Every Indian housewife is an entrepreneur in her true spirit. Their role as manager of the house can be related to the basic management techniques used in the business world of a small enterprise. The purpose of this paper is to identity the factors which influence women entrepreneurs and finding out the problems faced by them in Kalyana Karnataka Region.